2020
DOI: 10.3390/cancers12113078
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism Is a Predictive Factor for Better Clinical Outcomes in Patients with Advanced Hepatocellular Carcinoma Undergoing Lenvatinib Therapy

Abstract: Patients with advanced hepatocellular carcinoma (HCC) undergoing molecular targeted therapy often experience non-negligible adverse events (AEs). Paradoxically, certain AEs are reportedly associated with a good prognosis. We aimed to identify factors predictive of treatment duration and overall survival (OS) in patients with HCC undergoing lenvatinib therapy. Forty-six consecutive patients with advanced HCC who received lenvatinib therapy from April 2018 to November 2019 were prospectively followed until Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
(50 reference statements)
1
16
0
Order By: Relevance
“…patients in the longer survival group reported adverse effects (specifically, hand-foot skin reaction, hypertension and proteinuria) more frequently than in the lower survival population; this is consistent with other reports that correlate the onset of adverse events during lenvatinib with a better outcome. 29,30 These findings once again raise awareness about the management of adverse effects, especially taking into account the importance of maintaining a high relative dose intensity (70%-75%) in the first 4-8 weeks of treatment with lenvatinib in order to achieve a better outcome, both in response and survival. [31][32][33] Different from lenvatinib, the LEP index had no prognostic significance in patients treated with sorafenib.…”
Section: Discussionmentioning
confidence: 93%
“…patients in the longer survival group reported adverse effects (specifically, hand-foot skin reaction, hypertension and proteinuria) more frequently than in the lower survival population; this is consistent with other reports that correlate the onset of adverse events during lenvatinib with a better outcome. 29,30 These findings once again raise awareness about the management of adverse effects, especially taking into account the importance of maintaining a high relative dose intensity (70%-75%) in the first 4-8 weeks of treatment with lenvatinib in order to achieve a better outcome, both in response and survival. [31][32][33] Different from lenvatinib, the LEP index had no prognostic significance in patients treated with sorafenib.…”
Section: Discussionmentioning
confidence: 93%
“…Several predictors for the efficacy of lenvatinib (4-week relative dose intensity [ 19 ], AFP [ 20 , 21 ], ALBI grade [ 20 , 21 , 22 ], neutrophil-to-lymphocyte ratio [ 23 ], and occurrence of hypothyroidism [ 24 ]) have been reported previously. On radiological evaluation, obtaining OR by mRECIST evaluation has been reported to be an independent predictor of OS with other MTAs [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, one retrospective study showed that grade 1 and 2 thyroid dysfunction occurred in 6 (7.8%) and 14 (18.2%) patients, respectively, and grade 2 thyroid dysfunction was found to be a significantly unfavorable factor for PFS in a multivariate analysis [23]. On the other hand, another study showed that lenvatinib-induced hypothyroidism of grade 1, 2, and 3 was found in six (13%), 12 (26%), and one (2%) patients, respectively, and grade 2/3 hypothyroidism was found to be a favorable factor that affected OS in a multivariate analysis [57]. Thus, based on the obtained results of these studies, the relevance of thyroid dysfunction to the clinical outcomes remains controversial.…”
Section: Thyroid Dysfunctionmentioning
confidence: 98%